2021
DOI: 10.1016/j.scog.2021.100212
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes and subjective recovery of jumping to conclusions in schizophrenia

Abstract: This study investigated the effects of the bias known as jumping to conclusions (JTC) on objective functional outcomes as well as subjective assessments of quality of life (QoL) and personal recovery among a sample of patients diagnosed with schizophrenia. Specifically, this study assessed the variables of JTC, psychiatric symptoms, neurocognitive functioning, objective interpersonal and daily activities, vocational domains, subjective QoL, and personal recovery among 94 participants. Results showed that those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Analysis of 213 people with SMI in Spain found that, “the effects of social and cognitive functioning, although they may have had some degree of interaction, were relatively independent” in predicting gaining employment, which is frequently conceptualized as part of the purpose construct of recovery (Saavedra et al, 2016, p. 855). In a sample of people in Japan with schizophrenia Watanabe et al (2021) examined three components of social functioning (interpersonal functioning, employment, and daily life) and found that interpersonal functioning had a significant effect on assessment of personal recovery.…”
mentioning
confidence: 99%
“…Analysis of 213 people with SMI in Spain found that, “the effects of social and cognitive functioning, although they may have had some degree of interaction, were relatively independent” in predicting gaining employment, which is frequently conceptualized as part of the purpose construct of recovery (Saavedra et al, 2016, p. 855). In a sample of people in Japan with schizophrenia Watanabe et al (2021) examined three components of social functioning (interpersonal functioning, employment, and daily life) and found that interpersonal functioning had a significant effect on assessment of personal recovery.…”
mentioning
confidence: 99%